Low-Profile Dipole Antenna Integrated with Wideband Polarization Converter - Nkimbeng, Cho Hilary Scott; Wang, Heesu; Park, Ikmo (2025 IEEE International Workshop on Antenna Technology, iWAT 2025, 2025)
This paper presents the design of a low-profile dipole antenna integrated with a wideband polarization converter metasurface. The antenna consists of a modified dipole structure that includes two parasitic patches placed on the bottom side of a single-layer, ultra-thin substrate in a coplanar configuration. A 2 × 2 metasurface array is positioned on the top side of the substrate to convert linear polarization to circular polarization. Each unit cell of the metasurface consists of a complementary patch structure formed by etching out two diagonally oriented striplines from the metal square patch, resulting in a distinct chiseled pattern. These diagonal striplines are essential for creating 90° phase difference and achieving near-equal amplitude between orthogonal polarization components. The proposed antenna achieves a wide axial ratio (AR) bandwidth of 42.1% (4.06-6.22 GHz) and an impedance bandwidth of 44.2% (4.06-6.36 GHz), with a peak gain of 3.2 dBi at 5.2 GHz and a radiation efficiency of over 95% within the AR bandwidth.
Keywords: Axial ratio bandwidth; Low-profile; Low-profile dipole antennas; Metasurface; Parasitic patch; Polarization converters; Single layer; Thin substrate; Ultra-thin; Wide-band; dipole antenna; low profile; metasurface; polarization converter